ANALYSIS OF CHATGPT ACCEPTANCE FOR EDUCATION USING MODIFIED TECHNOLOGY ACCEPTANCE MODEL - Mahmud Rizal Mustofa; Siregar, Maria Ulfah (Jurnal Teknik Informatika (Jutif), 2024)
The presence of ChatGPT provides various benefits from all sectors including education. However, despite the various benefits obtained, many researchers argue that ChatGPT also has many significant drawbacks. This research aims to analize the effect of perceived threat, perceived ease of use, perceived usefulness, attitude toward using dan behavioral intention to use the system of ChatGPT in education. The TAM modification in this research is the addition of a perceived threat variable which refers to the problem of the research object.The population in this research is active students of Universitas Islam Negeri Sunan Kalijaga Yogyakarta. The sampling technique is carried out using probability sampling or simple random sampling. While the determination the number of samples in this study used a sample table so that 377 respondents were students from various faculties. The data used in this study were obtained by distributing questionnaires and analyzed using SEM-PLS with the help of SmartPLS 3 software. The result of this research show that perceived threat and perceived ease of use affect perceived usefulness, perceived ease of use and perceived usefulness affect attitude toward using and attitude toward using affects behavioral intention to use of ChatGPT in education.